Implementasi Pemberdayaan UMKM melalui Pengembangan Digitalisasi Teknologi dan Pemanfaatan Sumber Daya Lokal ‘Pisang’ di Desa Saringembat Tuban - Verend Sirlya; Maharani Ikaningtyas (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2025)
The empowerment of Micro, Small, and Medium Enterprises (MSMEs) plays a vital role in Indonesia's economic growth, including in Saringembat Village, Tuban Regency. Despite its significant potential, MSME actors in this village face challenges in adopting digital technology. Through the Community Service Program (KKNT), university students provide education and hands-on practice in MSME digitalization, focusing on the utilization of local resources, such as bananas, to enhance product competitiveness. The program includes socialization, training, and digital marketing through social media and e-commerce platforms. As a result, MSME actors successfully developed banana cookies as a flagship product with attractive branding, expanded market reach, and increased understanding of the importance of digitalization. This program has proven effective in improving operational efficiency and opening new market opportunities, although challenges related to digital literacy remain. It is recommended that ongoing support be provided to assist MSMEs in the digital era.